Dissipative nonlinear dynamics of ferromagnetic bilayer - Kovalev, A. S.; Ezerskaya, E. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
Within the framework of the classical Landau–Lifshitz equations with damping in the Landau form, the relaxation of highly excited magnetic multilayers, consisting of two ferromagnetic layers with magnetic anisotropy of the easy plane type and ferromagnetic exchange interaction between the layers, is analytically and numerically studied. It is shown that the relaxation of the energy and magnetization of the system is of a non-trivial behavior. In the region of strong excitation of the system, the time dependence of the magnetization is non-monotonic, and the smooth time dependencies of energy and magnetization are superimposed by oscillations associated with the essentially nonlinear dynamics of the magnetization vectors in the layers.